Whole Genome Studies Identify Solute Carrier Transporters in Cellular Susceptibility to Paclitaxel - Njiaju, Uchenna O. (2012)
OBJECTIVE: Clinical use of paclitaxel is limited by variable responses and the potential for significant toxicity. To date, studies of association between variants in candidate genes and paclitaxel effects have yielded conflicting results. We sought to evaluate relationships between global gene expression and paclitaxel sensitivity. METHODS: We utilized well-genotyped lymphoblastoid cell lines derived from the International HapMap Project to evaluate relationships between cellular susceptibility to paclitaxel and global gene expression. Cells were exposed to varying concentrations of paclitaxel to evaluate paclitaxel-induced cytotoxicity and apoptosis. Among the top genes, we identified solute carrier (SLC) genes associated with paclitaxel sensitivity and narrowed down the list to those that had single nucleotide polymorphisms (SNPs) associated with both their expression level of the SLC gene and also with paclitaxel sensitivity. We performed independent validation in an independent set of cell lines and also conducted functional studies using RNA interference. RESULTS: Of all genes associated with paclitaxel-induced cytotoxicity at p<0.05 (1713 genes), there was a significant enrichment of SLC genes (31 genes). A subset of SLC genes, namely SLC31A2, SLC43A1, SLC35A5, and SLC41A2, were associated with paclitaxel sensitivity and had regulating SNPs that were also associated with paclitaxel-induced cytotoxicity. Multivariate modeling demonstrated that those 4 SLC genes jointly explain 20% of the observed variability in paclitaxel susceptibility. Using RNA interference, we demonstrated increased paclitaxel susceptibility with knockdown of 3 SLC genes, SLC31A2, SLC35A5, and SLC41A2. CONCLUSIONS: Our findings are novel and lend further support to the role of transporters, specifically solute carriers in mediating cellular susceptibility to paclitaxel.